Bromine-Radical-Mediated Site-Selective Allylation of C(sp3)–H Bonds - Ueda, Mitsuhiro; Maeda, Ayami; Hamaoka, Kanako; Sasano, Mika; Fukuyama, Takahide; Ryu, Ilhyong (Synthesis, 2019)
The C(sp3)–H allylation of alkanes is investigated by using allyl bromides under radical reaction conditions. In many cases, methine C–H allylation preceded methylene and methyl C–H allylation with complete or a high degree of site selectivity. The C–H allylation of allylic compounds, such as allylbenzene, gives 1,5-dienes with the SH2′ reactions of the allyl radicals occurring at the less hindered carbon.
Keywords: C(sp3)–H allylation; bromine radicals; SH2 reaction; SH2′ reaction; site selectivity